Evolução da Aids na população jovem da Paraíba no período de 2007 a 2014 - Pereira, Ivoneide Lucena (2016)
The control of infection by HIV/Aids remains as a challenge for the public health and it involves several areas of knowledge, such as human rights, quality of life, medicine policies, industrial property, and diversity, among others. Infection by HIV/Aids is a phenomenon which occurrence mode impacts the moral, religious and ethical principles associating with topics concerning sexuality, drugs intake and marital morality. The beginning of the epidemic was directly associated with male homosexuals, injectable drug users and sex professionals, although in the last years the young population has had an increase on the notifications. Purpose: Analyze the epidemic of aids on the young population of Paraiba from 2007 to 2014 considering socio demographic and epidemiologic varieties. Methodology: It is an ecological study of the temporal series and quantitative approach made with the data bank of System Notification Information and National Grievances (Sinan), concerning the secondary data as for the notifications of the youth with aids aging from 15 to 24 years old, in the period from 2007 to 2014. The data base was composed by 329 registered cases and transported to the Excel chart. The socio demographic and epidemiological variables identified in the data bank have been submitted to descriptive statistics, the incidence rates and the relative risk of aids verified per micro region of the State. Results: aids infection among the youth in Paraiba showed a higher number of cases in macro region I (70, 5%), at age range from 22 to 24 years old (60, 4%), at the fundamental schooling level (52%), brown skinned (68%) and on the sexual transmission mode (71, 7%). It`s worth noticing cases among Indians (0, 9%) and concentration in the urban areas (90, 8%). Macro region I shows a greater rate of cases and relative risk superior to the global risk of the State in all temporary in relation to the other macro regions. 2007 draws attention to a high evolution on the incidence rate of cases in every macro regions of the State. The data have permitted visualize the temporal evolution of aids infection among the youth population of Paraiba. Conclusion: aids infection on the youth population in the State shows oscillations on its evolution tending to elevate the incidence rates and risks of infection with the virus at the macro regions of the State. The epidemiological and socio demographic aspects of the youth with aids reinforce the necessity of actions toward prevention and assistance to the young public.